2016
DOI: 10.3390/su8101016
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Mobility: Longitudinal Analysis of Built Environment on Transit Ridership

Abstract: Abstract:Given the concerns about urban mobility, traffic congestion, and greenhouse gas (GHG) emissions, extensive research has explored the relationship between the built environment and transit ridership. However, the nature of aggregation and the cross-sectional approach of the research rarely provide essential clues on the potential of a transit system as a sustainable mobility option. From the perspective of longitudinal sustainability, this paper develops regression models for rail transit stations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Bao et al divided bikesharing stations into five types based on their surrounding points of interest (POIs) before exploring bikesharing travel patterns and trip purposes; it was found that relatively little travel behavior information can be extracted from LDA model without classification compared with after classification ( 20 ). Subway and taxi data were analyzed simultaneously to uncover factors on human mobility depending on the means of transportation in Seoul, with stations divided into several subsets with similar ridership patterns ( 21 ). Compared with modeling for the entire data directly without further processing, two-step modeling, clustering first and then modeling, has greatly improved performance in relation to rationality and veracity of result unscrambling ( 12 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bao et al divided bikesharing stations into five types based on their surrounding points of interest (POIs) before exploring bikesharing travel patterns and trip purposes; it was found that relatively little travel behavior information can be extracted from LDA model without classification compared with after classification ( 20 ). Subway and taxi data were analyzed simultaneously to uncover factors on human mobility depending on the means of transportation in Seoul, with stations divided into several subsets with similar ridership patterns ( 21 ). Compared with modeling for the entire data directly without further processing, two-step modeling, clustering first and then modeling, has greatly improved performance in relation to rationality and veracity of result unscrambling ( 12 ).…”
Section: Related Workmentioning
confidence: 99%
“…The existing methods have been widely applied to investigate spatial variations in the nexus between transit ridership and ambient built environment. The ordinary least squares (OLS) regression model was the most common method in previous studies ( 21 ). Moreover, other traditional statistical models like the structural equation model (SEM), zero-inflated negative binomial model, hierarchical Bayesian models, and Poisson regression model were also frequently used in the field of transit ridership analysis ( 2 , 31 , 35 , 36 ).…”
Section: Related Workmentioning
confidence: 99%
“…Although rapid transit ridership involves count data, the preferable negative binomial regression and Poisson regression have been rarely used for station-level ridership analysis (Choi et al, 2012). The main reason is that count data models are perceived not to have any advantages for ridership analysis (Choi et al, 2012;Dill et al, 2013;Kim et al, 2016). Another violation of the assumptions underlying OLS regression analysis is that there is no correlation between the independent variables and the disturbance items.…”
Section: Introductionmentioning
confidence: 99%
“…In the Beijing case study developed by Wang et al [37], the intense population growth in suburban regions quadrupled individual transport emissions between 2000-2009 due to trip increases. The case study on land use near subway stations in Los Angeles conducted by Kim et al [38] demonstrated the link between the location of offices and shopping centers and the generation of travel. According to Dhakap and Schipper [17], urban mobility planning fails because it does not predict a decrease in vehicle inventory and the demand for travel; instead, it only provides infrastructure improvement directed to the most emitting mode, encouraging it.…”
Section: Data Transparency and Integrated Planningmentioning
confidence: 99%